Predicting cognitive ability in ageing cohorts using Type 2 diabetes genetic risk. Issue 6 (30th January 2014) - Luciano, M.; Mõttus, R.; Harris, S. E.; Davies, G.; Payton, A.; Ollier, W. E. R.; Horan, M. A.; Starr, J. M.; Porteous, D. J.; Pendleton, N.; Deary, I. J.
Abstract Aims To investigate whether there is overlap in the genetic determinants of Type 2 diabetes and cognitive ageing by testing whether a genetic risk score for Type 2 diabetes can predict variation in cognitive function in older people without dementia. Methods Type 2 diabetes genetic risk scores were estimated using various single nucleotide polymorphism significance inclusion criteria from an initial genome‐wide association study, the largest in Type 2 diabetes to date. Scores were available for 2775–3057 individuals, depending on the cognitive trait. Results Type 2 diabetes genetic risk was associated with self‐reported diabetes mellitus. Across varying single nucleotide polymorphism‐inclusion levels, a significant association between Type 2 diabetes genetic risk and change in general cognitive function was found (median r = 0.04); however, this was such that higher Type 2 diabetes genetic risk related to higher cognitive scores. Conclusions To investigate more fully the source of the often observed comorbidity between Type 2 diabetes and cognitive impairment, one direction for future research will be to use cognitive ability polygenic risk scores to predict Type 2 diabetes in line with the reverse causation hypothesis that people with lower pre‐morbid cognitive ability are more likely to develop Type 2 diabetes.